Corroboration assessments and recent progress towards integrative systematics: a reply to Farris and Carpenter - Faith, Daniel P.; Köhler, Frank; Puslednik, Louise; Ballard, J. W.o. (Zootaxa, 2012)
As part of the Zootaxa special issue on molecules and morphology in systematics, Faith et al. (2011) discussed how corroboration assessment can support integrative systematics. They argued that integrative systematics should be open to a wide variety of potential supporting evidence for phylogenetic (or species) hypotheses, with the condition that (p. 52) “there would be a requirement that all such supporting evidence be exposed to a skeptical assessment that, in effect, tries to ‘explain the evidence away’”. Faith et al. (2011) argued that corroboration assessment provides this critical examination of evidence, capturing the idea that supposed supporting evidence for an hypothesis is only impressive to the extent that the evidence cannot easily be accounted for by other factors, including chance. This characterization accords with Popper’s (1983: 238) idea that evidence that truly corroborates an hypothesis ‘should be improbable on our background knowledge’ (for discussion, see Faith 1992; Faith & Cranston 1992; Faith 2004, 2006).